Pengaruh Debt Default , Firm Size , Dan Prior Opinion Terhadap Penerimaan Opini Going Concern - Lukyanto Dwi Sandi; Adi Prasetyo; Eris Tri Kurniawati (Universitas Muhammadiyah Malang, 2017)
The purpose of this study is to examine the effect of debt default, firm size, prior opinion onacceptance of going concern audit opinion on companies listing on BEI. This type of research isassociative. The types and sources of data in this study are secondary data and Indonesia StockExchange. Technique of taking data is done with documentation. The result of this research isDebt Default have positive effect to the acceptance of going concern opinion, firm size does nothave an effect on the acceptance of going concern opinion, prior opinion has an effect on acceptance of going concern opinion.Keywords: debt default, firm size, prior opinion, going concern opinion